Maria Guilhermina Loureiro de Andrade: a trajetória profissional de uma educadora (1869/1913) - Carla Simone Chamon (2005)
This paper is a historiographical report on the professional life of Maria Guilhermina Loureiro de Andrade (1839-1929). She worked as a teacher, writer and translator in Rio de Janeiro, São Paulo and Minas Gerais during the second half of the XIX and in the early XX century. The purpose of this paper is to shed light on the life an intelectual/teacher whose work was distinguised by her decision to adopt a presbiterian reformed faith and whose professional work in the Brazilian education field during the aforementioned period was rather peculiar both because she graduated and specialized in educational issues and also because she focused her practice and reflexions on the educational field based on North American pedagogical standarts, thus bringing in and disseminating throughout Brazil elements of a pedagoy deemed modern. In the attempt to grasp an undertanding of the construction of Maria Guilherminas professional life and her insertion into educational field I have tried to pinpoint the social conditions experienced both by Guilhermina herself and also by sociability networks in which she was inscribed. Under such circunstances, her relation to religious faith, her convertions to reformed christianity and her liason with presbiterian missionaires and educators who had come from the USA to Brazil during the second half of the XIX century appeared to be decisive for her. Her initial contact with this missionaires and later her trip to the United States allowed her to familiarize with the North American pedagogical inventory. In addition, her religious status was the starting point from where she could read the world and focus on an education-oriented field pratice. This away, Maria Guilhermina got hold of knwoledge and practices taken from the North American educational inventory, distributing them and becoming at length an educational professional woman who at that time was considered competent enough to intervene in the educational field. She also became a translator/mediator between two cultural universes Brazil/United States thus contributing to restate the possibles of the Brazilian education.